Socialisation and citizenship preparation in vocational education: Pedagogic codes and democratic rights in VET-subjects. Issue 1 (2nd January 2020) - Nylund, Mattias; Ledman, Kristina; Rosvall, Per-Åke; Rönnlund, Maria
ABSTRACT: Previous studies of citizenship preparation in upper secondary school, including studies on vocational programmes, have primarily focused on general subjects. Potential and actual roles of vocational subjects in this context have received little attention, so we have little knowledge of what is likely a significant part of the citizenship preparation that occurs in vocational programmes. Drawing on the work of Basil Bernstein and ethnographic data, this study presents an analysis of socialisation processes in vocational elements of three vocational programmes in Swedish upper secondary school. The analysis addresses the formation of pedagogic codes in various vocational programmes and subjects, and how these codes condition students' practice of citizenship at individual, social and political levels. The results show how different pedagogic codes have different implications for the students' practice of citizenship, and thus raise questions about factors and processes that may either constrain or strengthen, this aspect in vocational subject classes.